Therapies for bronchiectasis: mechanisms and potential effects - Yu, Long; Zhu, Hong-rui; Jin, Xue-hang; Ding, Jin; Jin, Ting (Frontiers in Immunology, 2026)
Bronchiectasis is a complex and heterogeneous disease, and our current understanding of its pathophysiological mechanisms remains in its infancy. Currently, few specifically approved treatments for non-cystic fibrosis bronchiectasis are applied globally, and most guideline-recommended therapies have limited evidence of efficacy. Consequently, the development of new treatment methods is particularly urgent. To gain insight into new drugs under clinical development for adults with bronchiectasis, we conducted a review of the scientific literature and clinical trial registries. In this review, we discuss in detail the mechanisms and potential effects of these emerging therapies, which focus on their anti-inflammatory effects, enhancement of mucociliary clearance, and anti-infectious effects. Clinical research has revealed significant variability among patients, suggesting the need for a multidisciplinary and comprehensive approach. Future efforts should focus on patient stratification using biomarkers and clinical assessments, with an emphasis on precision medicine. Furthermore, it is essential to develop new antibiotics, innovative neutrophil-targeted therapies, and effective mucus-clearing agents to alleviate patient disease burden and minimize the risk of exacerbations.